Tourists’ Perception of Infectious Diseases in Malaysia (Asian Journal of Pharmaceutics (AJP), 2021)
Objective: This study evaluated the perceptions of infectious diseases among tourists about risk categories ofdifferent diseases. Materials and Methods: A cross-sectional study using a self-developed research instrumentwas designed and used to collect data from the tourists visiting Penang, Malaysia. Descriptive, comparative,and inferential statistics were performed using Statistical Package for the Social Sciences. Results: One-halfof the respondents perceived hepatitis A (50.3%), meningitis (52.3%), and typhoid fever (51.3%) as low-riskdiseases, while about 37% and 33% tourists considered dengue and HIV/AIDS as high-risk diseases, respectively.Conclusion: The results suggest that tourists perceived varied risk levels of infectious diseases in Malaysia,indicating that the tourists should take proper preventive measures to avoid contracting these diseases.